2014
DOI: 10.1371/journal.pone.0096558
|View full text |Cite
|
Sign up to set email alerts
|

Connexin Hemichannel Blockade Is Neuroprotective after Asphyxia in Preterm Fetal Sheep

Abstract: Asphyxia around the time of preterm birth is associated with neurodevelopmental disability. In this study, we tested the hypothesis that blockade of connexin hemichannels would improve recovery of brain activity and reduce cell loss after asphyxia in preterm fetal sheep. Asphyxia was induced by 25 min of complete umbilical cord occlusion in preterm fetal sheep (103–104 d gestational age). Connexin hemichannels were blocked by intracerebroventricular infusion of mimetic peptide starting 90 min after asphyxia at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 42 publications
3
56
0
Order By: Relevance
“…54 Peptide5 has previously been shown to reduce vessel leak and inflammation following central nervous system (CNS) injury, promote glial and neuronal survival, or provide improved functional outcomes in several CNS models. 24,25,28,29,55 (For a full review of hemichannel roles in CNS injury, see, e.g., Refs. 23, 25, 54, 56-59.…”
Section: Connexin43 Mimetic Peptide Preserves Retinal Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Peptide5 has previously been shown to reduce vessel leak and inflammation following central nervous system (CNS) injury, promote glial and neuronal survival, or provide improved functional outcomes in several CNS models. 24,25,28,29,55 (For a full review of hemichannel roles in CNS injury, see, e.g., Refs. 23, 25, 54, 56-59.…”
Section: Connexin43 Mimetic Peptide Preserves Retinal Functionmentioning
confidence: 99%
“…26,27 Peptide5, the Cx43 mimetic iovs.arvojournals.org j ISSN: 1552-5783 peptide used in this study, reduces lesion spread and inflammation and has neuroprotective effects following spinal cord injury leading to improved functional outcomes. 26,27 Local brain administration of Peptide5 via an intracerebroventricular catheter also led to significantly improved brain functional outcomes in a model of fetal sheep global cerebral ischemia induced by bilateral carotid artery occlusion 28 and asphyxia 29 as well as in a retinal ischemia-reperfusion rat model where systemic administration of Peptide5 prevented vessel leak and reduced inflammation, with a downstream neuroprotective effect on retinal ganglion cells. 24 The present study investigated the effect of blocking Cx43 hemichannels on retinal function in the light-damaged albino rat, an acute injury model but one that shows some of the inflammation characteristics of AMD.…”
mentioning
confidence: 99%
“…The timing of Panx1 channel or HC opening as a result of ischemia, for example, remains unclear, because much of the literature does not distinguish between events occurring during, as opposed to those occurring after, ischemia. This may be significant as in vivo, an upregulation of Cx and associated HC-mediated events appear to be important in reperfusion injury, but HC opening may turn out to be limited or have relatively little impact during ischemia itself [98][99][100][101].…”
Section: General Concepts Of Connexin and Pannexin Signalingmentioning
confidence: 99%
“…By using Cx43 targeting peptides, it has been demonstrated that blocking HCs can counteract several pathological processes, such as glutamate and ATP release, excitotoxicity, and apoptosis, and it can influence the neuro-inflammatory process [47,52,67,90,336,367]. In addition, their application has been demonstrated to resort to beneficial effects in in vitro and in vivo models of CNS pathologies, including brain asphyxia [100], brain and retina ischemia [98,368,369], epilepsy [364,370], Alzheimer's Disease [57], optic neuropathy [371], spinal cord injury [88,337], and inflammation or ischemia-induced vascular leakage/inflammation-induced BBB permeability [89,98].…”
Section: Contribution Of Astroglial Connexins To Vasomotor Control Anmentioning
confidence: 99%
“…Additionally, recent studies have shown that oxaliplatin can affect the expression levels of GJs in astrocytes (Yoon et al, 2013) and dorsal root ganglia (DRG) satellite glial cells (Warwick and Hanani, 2013), while GJ blockage by carbenoxolone results in analgesic-like effects (Rouach et al, 2003;Vessey et al, 2004). Furthermore, GJ hemichannel blockade was found to be neuroprotective in some cases of global cerebral ischemia in nearterm fetal sheep (Davidson et al, 2014), while gap junctional communication could counteract the effects of the anti-tumor agent cisplatin (homologous to oxaliplatin) (Broomand et al, 2009). Recent studies of taxol and oxaliplatin neurotoxicity suggested that GJ blockers may have potential in treating chemotherapy-induced neuropathic pain (Warwick and Hanani, 2013).…”
Section: Introductionmentioning
confidence: 99%